1998
DOI: 10.1007/s002340050665
|View full text |Cite
|
Sign up to set email alerts
|

Slow-growing labyrinthine masses: contribution of MRI to diagnosis, follow-up and treatment

Abstract: We report the use of MRI in the diagnosis, follow-up and therapeutic management of three cases of intralabyrinthine Schwannoma. The diagnosis was based on the history and initial and follow-up MRI findings. The main feature suggesting the diagnosis was a nodular intralabyrinthine mass of low signal intensity on T2-weighted images, and high or isointense signal on T1-weighted images (relative to cerebrospinal fluid), which showed contrast enhancement. Follow-up imaging showed growth of the tumour in one patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…12,14,16,17,22,23,26 More advanced imaging and characterization with high-resolution T2 and gradient recalled-echo sequences appeared in the literature in the early 2000s. 1,21,[28][29][30][31] Some reports have suggested that the lesions can be invisible on T2 and even postgadolinium T1-weighted images. 10,17,26 This insensitivity may have been due to section thickness and less optimized imaging sequences at that time.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,16,17,22,23,26 More advanced imaging and characterization with high-resolution T2 and gradient recalled-echo sequences appeared in the literature in the early 2000s. 1,21,[28][29][30][31] Some reports have suggested that the lesions can be invisible on T2 and even postgadolinium T1-weighted images. 10,17,26 This insensitivity may have been due to section thickness and less optimized imaging sequences at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Preferential growth in the scala tympani is thought to be due to the proximity of the nerve to the scala tympani in the region where it leaves the osseous spiral lamina, called the habenula perforate, which runs toward the organ of Corti 28 (Fig 6). From the scala tympani, these lesions may then extend into the scala vestibuli 17,29 (Fig 2). In 8 of the 16 ILSs involving both scalae, the scala tympani component was larger than the scala vestibuli (Figs 1 and 2) component; in 7 other cases, the scala tympani and scala vestibuli component had the same size.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of reports, mainly case reports and small series of less than 10 subjects, described the imaging findings of ILSs. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] One larger series of 28 cases published by Kennedy et al 23 focused on management and classification of these lesions. However, only 15 cases of this series met the above-described stringent criteria of ILS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of this disease is still a matter of debate: only 1 of 893 cases has been described in an autopsy study (prevalence of 0.1%) [4] . Further, only 3 of 800 patients who had suggestive symptoms of Meniere's disease and who underwent magnetic resonance imaging (MRI) were found to have ILS (prevalence of 0.4%) [5] . Salzman et al [6] analyzed 45 cases of ILS confirmed by MRI that were collected over 14 years.…”
Section: Introductionmentioning
confidence: 99%